Conservative management of single foetal death in multiple pregnancy at a tertiary care hospital in Bangladesh: Two case reports (Bangladesh Medical Journal, 2017)
The single fetal death in multiple pregnancy is not rare. Death of one fetus in multiple pregnancy increases the risk of mortality and morbidity of the surviving fetus. This might pose management challenge to the obstetrician. It is a cause of great concern and psychological stress to the parents. Proper diagnosis and intervention in appropriate time can improve the maternal and neonatal outcome. Adequate counseling, psychological support and close follow up are mandatory. There are potential complications to the mother and the surviving twin.Bangladesh Med J. 2016 Sep; 45 (3): 172-174